(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2011)
Background: The incidence of vaso vagal reaction among the whole blood donors are common. Few percent of these reaction may progress to syncope. Objectives: To evaluate the incidence of vaso-vagal reaction (VVR) among whole blood donors. Methods: This prospective, observational study was done in the department of transfusion medicine in Bangabandhu Sheikh Mujib Medical University from 01-04-2008 to 31-03-2009. Total 19553 blood donors were observed for vaso-vagal reaction. Results: The incidence of vaso-vagal reaction was 0.37%, in male 0.33% and in female it was 0.67%. Female donors were significantly more prone to develop vasovagal reaction (p=0.001). 78.8% of donors were first time donor and 28.8% were repeat donor. The clinical character of the symptoms according to frequency was- Sweating (86.3%), Nausea/ Vomiting (80.8%), Pallor (67.1%), Dizziness (39.7%), Loss of consciousness and fainting, increased rate of respiration (30.1%), anxiety presented (16.4%) and vertigo (1.4%). Conclusion: Although the incidence of vasovagal reactions in our study is lower than other studies, it is important to follow strict donor selection criteria and ensure careful monitoring during and immediate after the donation process to avoid the fatal consequences. Key words: Vaso-vagal reaction; donor reaction; blood donation. DOI: http://dx.doi.org/10.3329/bsmmuj.v4i2.8640 BSMMU J 2011; 4(2):106-109